(untitled) (Razão e Fé, 2021)
The object of our study is the relationship between theology and liberation. The issue of liberation is analyzed in the historical and systematic view of Latin American theology and its contributions in Latin America. For this purpose, we will examine the concepts of liberation and integral development, liberation in Latin American theology, indicating paths and perspectives for Latin American liberation theology.